Inverse Association Between Hypothalamic N-Acetyl Aspartate/Creatine Ratio and Indices of Body Mass in Adolescents with Obesity. Issue 3 (9th December 2021) - Neves, Thaysa Mara Gazzotto; Simoes, Estefania; Otaduy, Maria Concepcíon García; Calfat, Elie Leal de Barros; Bertolazzi, Pâmela; da Costa, Naomi Antunes; Duran, Fábio Luís de Souza; Correia-Lima, Joanna; Martin, Maria da Graça Morais; Seelander, Marília Cerqueira Leite; Otani, Victor Henrique Oyamada; Otani, Thais Zélia dos Santos; et al.
ABSTRACT: Background: Approximately 10% of adolescents worldwide are overweight or obese, hence the urgent and universal need to elucidate possible mechanisms that lead to obesity in the adolescent population. Objectives: We examined the hypothalamic metabolism and its relationship with physical development in obese and eutrophic adolescents. Methods: We performed a case-control study with 115 adolescents between 11 and 18 years of age, to compare obese (BMI z-score ≥ 2) and nonobese individuals (eutrophic controls; BMI z-score ≤ 1). The following hypothalamic metabolite ratios were examined as primary outcomes: glutamate/creatine (Cr), the sum of glutamate and glutamine/Cr, N-acetylaspartate (NAA)/Cr, myoinositol/Cr, and total choline/Cr (glycerophosphocholine + phosphocholine/Cr), quantified by magnetic resonance spectroscopy. BMI z-scores, pubertal status, and scores on the Yale Food Addiction Scale, the Binge Eating Scale, and the Child Depression Inventory were assessed as secondary outcomes. Pearson coefficients ( r ) or nonparametric Spearman correlation ( rho ) analyses were performed between hypothalamic metabolite ratios and other parameters, such as BMI z-scores, physical development, food habits, depression symptoms, and serum protein concentrations (cytokines, hormones, and neuropeptides). Results: Adolescents with obesity showed a lower hypothalamic NAA/Cr ratio (0.70 ± 0.19) compared to their eutrophic counterparts (0.84 ± 0.20; P = 0.004). The NAA/Cr ratio was negatively correlated with BMI z-scores ( r = −0.25; P = 0.03) and serum insulin ( rho = −0.27; P = 0.04), C-peptide ( rho = −0.26; P = 0.04), amylin ( r = −0.27; P = 0.04), ghrelin ( rho = −0.30; P = 0.02), and neuropeptide Y ( r = −0.27; P = 0.04). Also, the NAA/Cr ratio was positively correlated with circulating IL-8 levels ( rho = 0.26; P = 0.04). Conclusions: High BMI z-scores are associated with lower hypothalamic NAA/Cr ratios. The negative correlations found between the NAA/Cr ratio and serum cytokines, hormones, and neuropeptides suggest a broad cross-talk linking hormonal imbalances, neurohumoral alterations, and hypothalamic functions in adolescents with obesity.